Malignant melanotic schwannoma of the cervical spinal cord: a case report - Sihan Chen; Yiting Wei (BMC Neurology, 2024)
Abstract Spinal cord malignant melanotic schwannoma (MMNST) is a rare central nervous system tumor that originates from the spinal cord or spinal myelin sheath cells and can produce melanin. This type of tumor is usually highly aggressive and malignant, with a poor prognosis. The clinical manifestations of spinal cord MMNST are mainly pain, paresthesia, muscle weakness, muscle atrophy, etc., and symptoms of spinal cord compression, such as intestinal and bladder dysfunction, paraplegia, etc. Early detection of tumor lesions can facilitate tumor removal, improve patients’ quality of life, and prolong patients’ survival. In this case report, a 27-year-old young woman was diagnosed with MMNST of the cervical spinal cord due to weakness of her limbs in our hospital, and underwent surgical resection. The patient’s limbs returned to normal after surgery. It is worth mentioning that the patient visited our hospital 7 months ago for “right upper limb pain for 3 days” and was diagnosed with a cervical spine space-occupying lesion at the same position this time, but the pathology report was “hemosiderosis”. This case report aims to raise awareness of the problem of spinal cord MMNST and contribute to greater knowledge of this rare tumor.